Corporate Restructuring in Japan : An Event-Study Analysis - Chan-Lau, Jorge (IMF Working Papers; Working Paper ;, 2001)
The implementation of the Commercial Rehabilitation Law (CRL) on April 1, 2000 was considered a key event in setting up the official infrastructure supporting corporate restructuring in Japan. This study evaluates the stock price impact of restructuring announcements before and after the CRL implementation using event-study analysis. Following the CRL implementation, the results suggest an improvement in market credibility of restructuring announcements based on improvements in disclosure, mergers, and to a lesser extent, labor force reductions. In contrast, credibility of restructuring announcements aimed at reducing excess capital deteriorated.